Microstructural, mechanical and electrochemical characterisation of biomaterial ASTM F745 cast by vacuum - Gregorutti, Ricardo Walter (2012)
Countergravity low pressure casting (CLA) was performed to enhance the properties of ASTMF745 stainless steel (SS), which is usually used as biomaterial. The macro- and microstructureswere compared with those obtained by the conventional process of investment casting (IC). TheSS cast by CLA (SSCLA) exhibited a smaller size of solidification cell and finer dendriticmicrostructure. The average of its dendritic primary spacing was 110·4 mm, while for the same steel cast by IC (SSIC), it was 186·7 μm. The density of non-metallic inclusions δ in the SSCLA was 717 I mm -2, being the majority of them smaller than 1·5 mm. In the case of SSIC, dI was 852 I mm -2, with a size distribution of up to 8 μm. The SSCLA showed a higher breakdown potential than the SSIC, the values being 0·p300 and 0·210 V(saturated calomel electrode) respectively, which means a higher resistance to suffer localised corrosion. Finely, the CLA process also allowed obtaining better mechanical properties.